PENGARUH MODEL PROJECT BASED LEARNING (PjBL) DAN LITERASI DIGITAL TERHADAP KEMAMPUAN BERPIKIR KRITIS PESERTA DIDIK KELAS V MATA PELAJARAN IPAS SDN TOMANG 03 - Nurwihayati Nurwihayati; Tri Isti Hartini; Irdalisa Irdalisa (SPEKTRA: Jurnal Kajian Pendidikan Sains, 2025)
This study aims to determine and describe the influence of learning models Project Based Learning (PjBL) on Critical Thinking Skills, the influence of Digital Literacy to Ability and there is an interaction between Project Based Learning (PjBL) with Digital Literacy. The method used is a quantitative method. The instrument used is a test. The test was given to students of SD Negeri Tomang 03 class VA and VB. The data analysis used was a two-way ANOVA test. The results of this study showed that there was an influence and significance between the influence of the learning model Project Based Learning (PjBL) on students' critical thinking skills with Fhit values ​​> Ftab 5.97> 4.14, there is a significant influence on digital literacy on students' critical thinking skills with Fhit > Ftab 33.41 > 4.14, there is no interaction between Project Based Learning (PjBL) with Digital Literacy students with Fhit < Ftab -0.27 < 4.14. Learning model Project Based Learning (PjBL) has an influence on students' critical thinking skills, so that Project Based Learning (PjBL) will contribute to students' critical thinking skills. Digital Literacy has an influence on students' critical thinking skills, so that with digital literacy which will contribute to students' thinking skills. The higher the digital literacy, the higher the students, then students' critical thinking skills will also increase.